Inverse problem of spectral analysis and the non-Abelian chains of nonlinear equations - Berezansky, Yu. M.; Gekhtman, M. I. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
Using the method of the inverse spectral problem we construct solutions of the Cauchy problem for some systems of nonlinear difference-differential equations with operator unknowns in the semi-infinite case.